Monitoring the impact of COVID-19 in Myanmar: Agricultural input retailers - Mid-June and early July 2020 survey rounds - Goeb, Joseph; Zu, A Myint; Synt, Nang Lun Kham; Boughton, Duncan; Maredia, Mywish K. (International Food Policy Research Institute, 2020)
Phone surveys were conducted with input retailers from Shan, Kachin, Bago, Ayeyarwady, Sagaing, and Mandalay between 17 and 20 June and again between 6 and 8 July 2020 to understand and monitor the effects of the COVID-19 crisis on the agricultural input sector.